The Problematics of Simple Lawsuit Implementation To Reduce Civil Cases In Supreme Court - Sugeng, Bambang; Vandawati Ch., Zahry (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2020)
This research has purpose to analyze the implementation of a simple lawsuit settlement to reduce the accumulation of civil cases in the Supreme Court. Also to aanalyze the constraints and obstacles in the application of simple claim resolution to reduce the buildup of civil cases and investigate the constraints and obstacles in the application of simple claim resolution to reduce the buildup of civil cases. This research is normative legal research that used the approach of statute approach and conceptual approach. The result of this research indicated that the implementation of simple lawsuit mechanismin court process could be quite helpful for citizen to settle the civil cases on state court with a quick process, simple system and low cost. In the context of implementing a simple lawsuit mechanism in court proceedings, there are several obstacles and have not maximally utilized in society, such as the minimum limit for the value of material claims is at most Rp. 200,000,000.00 (two hundred million rupiahs). [Penelitian ini bertujuan untuk menganalisis pelaksanaan penyelesaian gugatan sederhana yang dapat digunakan untuk mengurangi penumpukan perkara perdata di Mahkamah Agung, serta menganalisis kendala dan kendala dalam penerapan penyelesaian gugatan sederhana guna mengurangi penumpukan perkara perdata. kasus perdata dan menganalisis kendala dan hambatan dalam penerapan penyelesaian gugatan sederhana untuk mengurangi penumpukan kasus perdata. Penelitian ini merupakan penelitian hukum normatif dengan menggunakan pendekatan statuta dan pendekatan konseptual. Hasil penelitian ini menunjukkan bahwa penerapan mekanisme gugatan sederhana dalam proses peradilan dapat sangat membantu warga negara untuk menyelesaikan perkara perdata di pengadilan negara dengan proses yang cepat, sistem yang sederhana dan biaya yang murah. Dalam rangka penerapan mekanisme gugatan sederhana di pengadilan. Dalam proses persidangan terdapat beberapa kendala dan belum dimanfaatkan secara maksimal di masyarakat, antara lain, batas minimal nilai klaim materiil paling banyak Rp. 200.000.000.00 (dua ratus juta rupiah).]